PERFORMA PEMBENIHAN DAN PEMELIHARAAN LARVA IKAN BAWAL BINTANG (Trachinotus blochii) DI BALAI BESAR PERIKANAN BUDIDAYA LAUT (BBPBL) LAMPUNG - Annisa Bias Cahyanurani; Diana Mahkota; Syofriani Syofriani; Teguh Harijono (Universitas Muhammadiyah Gresik, 2022)
Pomfret fish (Tracinotus blochii) is a new commodity that has the opportunity to be developed in Indonesia with market demand and a fairly high price. In cultivation activities, quality seeds play an important role in the success of cultivation. This study aims to see the performance of hatchery and rearing of star pomfret larvae through parameters of egg fertilization degree, egg hatching rate and survival rate of star pomfret larvae. The research method used is a survey method, data is collected through observation, documentation, interviews and direct participation in star pomfret hatchery activities. The data obtained were analyzed descriptively. The hatchery of star pomfret through natural spawning during the study had good performance starting from the degree of fertilization, hatching rate and survival rate of larvae. The total eggs produced in the star pomfret hatchery reached 680,000 eggs with a Fertilization Rate (FR) of 74.5% and a Hatching Rate (HR) of 85.78%. After rearing larvae for 28 days, the survival rate of star pomfret larvae was 33.75%. This is supported by the water quality during maintenance which shows the optimal range.